Entre la autoría y la redención: abordajes críticos acerca de nikos kazantzakis - Bernardes, Carolina Dônega [UNESP] (My University, 2016)
This article aims to reflect on the reasons that lead canonical criticism of Nikos Kazantzakis to worry a lot more about unraveling the author's personality and less about his own work, to which it addresses, often as an object for elucidating the aesthetic and philosophical project of the author. We propose to demonstrate further that the treatment to Kazantzakis and his work is not only due to the position of criticism, but rather shows a trend encouraged by the author, who finds in literature the meta-political action for personal redemption, and to work towards collective salvation in times of crisis.
Between the authorship and redemption: Critical approaches about Nikos Kazantzakis
Keywords: Authorship; Meta-political; Nikos Kazantzakis; Redemption